The Effect of Organic and Inorganic Fertilizers to P-Uptake and Yield of Rice on Two Farming Systems at Sukoharjo - Hartati, Sri; Sumani, Sumani; Hendrata, Henricus EA (Caraka Tani - Jurnal Ilmu Ilmu Pertanian, 2014)
This study aims to determine the effect of organic and inorganic fertilizers and cropping systems on P uptake and growth and yield of rice determine the most optimum. The research was conducted in paddy fields in the village of Subdistrict Wotgaleh Sukoharjo Sukoharjo in February 2013 to May 2013 . This research is using RCBD (Randomized Complete Block Design) with two factors . The first factor is the culture system consisting of two levels are conventional systems ( B1 ) andÂ SRI systems ( System of Rice Intensification ) ( B2 ) . The second factor is the balance of organic and inorganic fertilizers ( P ) consisting of five levels are : ( P1 ) 100 % organic fertilizer ( Petroganik : 10 tons / ha ) , ( P2 ) 25 % organic fertilizer ( Petroganik : 2.5 tons / ha ) + 75 % inorganic fertilizer ( Phonska : 225 kg / ha ) + Urea : 150 kg / ha , ( P3 ) 50 % organic fertilizer ( Petroganik : 5 tons / ha ) + 50 % inorganic fertilizer ( Phonska : 150 kg / ha ) + Urea : 100 kg / ha , ( P4 ) 75 % organic fertilizer ( Petroganik : 7.5 tons / ha ) + 25 % inorganic fertilizer ( Phonska : 75 kg / ha ) + Urea : 50 kg / ha , ( P5 ) 100 % inorganic fertilizer ( Phonska : 300 kg / ha ) + Urea : 200 kg / ha . Parameters measured were available P , soil pH ( H2O ) , P network , stover dry weight , P uptake , total tiller number , and dry weight of harvested grain. The results showed that P uptake in conventional cropping systems is higher than the SRI cultivation system . P uptake in conventional cultivation of 0.135 g / clump whereas P uptake in SRI cultivation of 0.074 g / clump . Balance of organic and inorganic fertilizer with the highest P uptake was achieved in 100 % inorganic fertilizer , Phonska : 300 kg / ha + urea : 200 kg / ha which is 0.134 g / clump . The highest weight of dry grain harvest was achieved in the treatment of conventional cultivation system with 25 % organic fertilizer ( 2.5 t / ha Petroganik) and 7575 % inorganic fertilizer ( 225 kg / ha of fertilizer Phonska and 150 kg / ha urea ) that is equal to 12.98 tons / ha